\(\left(x-5\right)^4=\left(x-5\right)^6\)
=>\(\left(x-5\right)^4-\left(x-5\right)^6=0\)
=>\(\left(x-5\right)^4\left[1-\left(x-5\right)^2\right]=0\)
=>\(\left(x-5\right)^4\left(1-x+5\right)\left(1+x-5\right)=0\)
=>\(\left(x-5\right)^4\left(6-x\right)\left(x-4\right)=0\)
=>(x-5)4=0 hoặc 6-x=0 hoặc x-4=0
=>x=5 hoặc x=6 hoặc x=4
Bài này mình giải trình độ hơi cao so với lớp 6 nhưng bạn đọc kĩ sẽ hiểu :)
x4 - 625 = x6 - 15625
x6 - x4 = 15625-625
x6 - x4 = 15000
x6 - x4 = 56 - 54
Vậy x = 5
ta có: (x-5)4=(x-5)6
mà 4<6, x-5=x-5 và (x-5)4=(x+5)6
<=> x-5=1 ,x-5=-1, x-5=0
<=> x=6 ,x=4 ,x=5
suy ra x=6;4;5
\(\left(x-5\right)^4=\left(x-5\right)^6\)
TH1: \(x-5=1\Rightarrow x=6\)
\(x-5=-1\Rightarrow x=4\)
\(x-5=0\Rightarrow x=5\)
Vậy:...